A decision support system for business location based on open GIS technology and data - Ghiţa, Cornel (Managing global transitions, 2014)
This article presents the architecture, features, and operating mode of a DSS (Decision Support System) aiming to assist entrepreneurs and managers in the process of location decision making. The research assembled concepts derived from theory, findings of empirical studies, together with open GIS (Geographical Information System) software and data, and modelled them into a DSS software tool, according to an original methodology and design. The users are guided step-by-step to input information on their businesses into the DSS (industry, preferences for land-use areas and facility types, weights of key location factors), and are returned two sets of results: one based on own options, and another one aggregate for the industry they operate in. The results consist in the top five locations for the user's firm, as well as for the industry, depicted both in a graphical report (map) and a text report (explanation of results).
Keywords: informatika; information science; decision support system for business location; informacijski sistemi; open-source GIS software; geografski informacijski sistemi; podpora odločanju; odprta koda; lokacije; metropolitan areas